The buffalo soldier - Garland, Sherry (Pelican Pub. Co., 2006)
Realizing that his future lies in owning land, not just being free, a young man raised as a slave becomes a buffalo soldier--a member of an all-black cavalry regiment formed to protect white settlers from Indians, bandits, and outlaws, and that later fought in the Spanish-American War. Includes historical note.